Effects of real and imagined contact under conditions of socially acceptable prejudice - West, K (2010)
The objective of this thesis was to examine the effectiveness of contact and imagined contact (a derivative of direct contact) in reducing intergroup prejudice when the prejudice in question is deemed socially acceptable. Studies focused on two populations that are targets of socially acceptable, prejudice – people suffering from schizophrenia in the U.K., and homosexual men in Jamaica. These target groups were selected because they are similar in that they are both targets of socially acceptable prejudice, but also because of their differences in that the stereotypes associated with them are quite dissimilar. The first part of the thesis empirically tested the assumption that the aforementioned populations are targets of socially acceptable prejudice. Two cross-sectional studies, one of which was also cross-cultural, measured motivation to control prejudice against these target groups, and compared it to motivation to control prejudice against targets of socially unacceptable prejudice. I found that motivation to control prejudice against people with schizophrenia in the U.K. was lower than motivation to control prejudice against Black people in the U.K. Also, motivation to control prejudice against homosexual men was higher in the U.K. and the U.S.A. than in Jamaica, and differences in motivation to control unspecified prejudice were significantly smaller. The second part examined the association between actual contact and prejudice for both populations. Two cross-sectional studies, one of which was also cross-cultural, found that contact was associated with less prejudice. This effect was mediated by intergroup anxiety in all cases, and also by fear in the case of people with schizophrenia. Furthermore, I found that contact was more strongly negatively associated with anti-homosexual prejudice in Jamaica, where the prejudice is socially acceptable, than it was in Britain, where the prejudice is not socially acceptable. The third part tested the effect of imagined contact, a form of extended contact, on prejudice against people with schizophrenia. Four experimental studies demonstrated that imagined contact can be an effective means of reducing prejudice against this group. However imagined contact must be conducted in very specific ways, otherwise it has the potential to increase prejudice against people with schizophrenia.